ON THE CRIMINALIZATION OF INAPPROPRIATE USE OF BUDGETARY FUNDS - Zhanat Askarovna, Мамитоа (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article deals with the problems of implementing certain provisions of international agreements into the criminal legislation of the Republic of Kazakhstan, in particular on the criminalization of inappropriate use of the state funds